Aptameric biosensor for the sensitive detection of major shrimp allergen, tropomyosin. (1st June 2020) - Chinnappan, Raja; Rahamn, Anas Abdel; AlZabn, Razan; Kamath, Sandip; Lopata, Andreas L.; Abu-Salah, Khalid M.; Zourob, Mohammed
Highlights: Graphene oxide was used as sensing platform to probe the short aptamer for sensitive target binding. The short truncated aptamers has four-fold high affinity (30 nM) compared to the full-length aptamer. The sensor specifically detect TM in the duration of 30 min with LOD of 2 nM. Tropomyosin contaminated liquid food were detected accurately (~97%). Abstract: The development of a sensitive and rapid detection approach for allergens in various food matrices is essential to assist patients in managing their allergies. The most common methods used for allergen detection are based on immunoassays, PCR and mass spectrometry. However, all of them are very complex and time-consuming. Herein, an aptamer biosensor for the detection of the major shrimp allergen tropomyosin (TM) was developed. Graphene oxide (GO) was used as a platform for screening of the minimal-length aptamer sequence required for high-affinity target binding. A fluorescein dye labeled GO quenches the truncated aptamer by π-stacking interactions. After the addition of TM, the fluorescence was restored due to the competitive binding of the aptamer to GO. One of the truncated aptamers was found to bind to TM with four-fold higher affinity (30 nM) compared to the full-length aptamer (124 nM), with a limit of detection (LOD) of 2 nM. The aptamer-based sensor demonstrates the sensitive, selective, and specific detection of TM in 30 min. The performance of the sensor was confirmed using TM spiked chicken soup, resulting in a high percentage recovery (~97 ± 10%). The association of GO and labelled aptamer sensor platform has shown the rapid detection of TM in food, which is compared to other methods very sensitive, specific and performs in high throughput application.